2017
DOI: 10.1073/pnas.1611958114
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of immobilized chemokine CXCL12 in the regulation of the humoral immune response

Abstract: Chemokines control the migration of a large array of cells by binding to specific receptors on cell surfaces. The biological function of chemokines also depends on interactions between nonreceptor binding domains and proteoglycans, which mediate chemokine immobilization on cellular or extracellular surfaces and formation of fixed gradients. Chemokine gradients regulate synchronous cell motility and integrin-dependent cell adhesion. Of the various chemokines, CXCL12 has a unique structure because its receptorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…Increased MBC differentiation, together with impaired GC B cell expansion, was also found when LZ B cells cannot sense IL21 and when LZ to DZ migration is abrogated by impaired CXCR4 signaling (Bannard et al, 2013;Barinov et al, 2017;Linterman et al, 2010;Zotos et al, 2010). In both scenarios, antigen affinity was reduced, possibly favoring MBC differentiation (Shinnakasu et al, 2016;Weisel et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Increased MBC differentiation, together with impaired GC B cell expansion, was also found when LZ B cells cannot sense IL21 and when LZ to DZ migration is abrogated by impaired CXCR4 signaling (Bannard et al, 2013;Barinov et al, 2017;Linterman et al, 2010;Zotos et al, 2010). In both scenarios, antigen affinity was reduced, possibly favoring MBC differentiation (Shinnakasu et al, 2016;Weisel et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Their ability to bind chemokines influences chemokine/receptor interactions; chemokine half‐life in a tissue or tissue compartment; how, and where, a chemokine operates in vivo ; and the type of cell movement or adhesion it stimulates . They are essential for maintaining interstitial chemokine functions and gradients and for the presentation of chemokines on endothelial surfaces, preventing them being washed away by the blood and so allowing them to drive leukocyte arrest and extravasation . Some chemokines, such as CCL21, are very ‘sticky’ and become rapidly immobilized, while others, such as CCL19, which activates the same receptor as CCL21, likely diffuse more readily through tissues .…”
Section: Gags Oligomerization and Post‐translational Modificationmentioning
confidence: 99%
“…Similar to the CXCR4 knockout, it was shown that for CXCL12 gagtm mice, in which CXCL12 is unable to bind cellular or extracellular surfaces, magnitude of the germinal center reactions is normal but affinity maturation is less effective [67]. Two observations reported in this study are particularly relevant here.…”
Section: Discussionmentioning
confidence: 52%
“…Together with CXCR4, CD86 is currently the method of choice to gate LZ and DZ GC B cells by flow cytometry (e.g. [18,54,[64][65][66][67]). Nevertheless, some questions regarding CXCR4 expression heterogeneity remain unanswered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation